1989
DOI: 10.1083/jcb.108.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Addition of truncated oligosaccharides to influenza virus hemagglutinin results in its temperature-conditional cell-surface expression.

Abstract: we described the isolation and initial characterization of seven Chinese hamster ovary cell lines that are temperature conditional for the cell-surface expression of influenza virus hemagglutinin (HA) and other integral membrane glycoproteins. Two of these cell lines appeared to be defective for the synthesis and/or addition of mannose-rich oligosaccharide chains to nascent glycoproteins. In this paper we show that at both 32 and 39°C the two mutant cell lines accumulate a truncated version, MansGlcNAc2, of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…However, this does not explain the defect in End4 mutants, because HA folded and trimerized at the same rate in V.24.1 and wild-type cells at the restrictive temperature. The failure to secrete could also be related to unusual protein glycosylation, since Hearing et al (19,20) reported that addition of truncated N-linked oligosaccharides to HA impaired secretion in a temperaturesensitive mutant of CHO cells. However, in the present work, and in previous studies (39,56), we have not observed any unusual electrophoretic migration of newly synthesized glycoproteins in SDS-polyacrylamide gels that would suggest aberrant or heterogeneous oligosaccharides were present on glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not explain the defect in End4 mutants, because HA folded and trimerized at the same rate in V.24.1 and wild-type cells at the restrictive temperature. The failure to secrete could also be related to unusual protein glycosylation, since Hearing et al (19,20) reported that addition of truncated N-linked oligosaccharides to HA impaired secretion in a temperaturesensitive mutant of CHO cells. However, in the present work, and in previous studies (39,56), we have not observed any unusual electrophoretic migration of newly synthesized glycoproteins in SDS-polyacrylamide gels that would suggest aberrant or heterogeneous oligosaccharides were present on glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cell lines in yeast and mammalian cells have been isolated with defects in synthesis, transfer, and trimming of N-linked core carbohydrates (Reitman et al, 1982;Stanley, 1984;Hearing et al, 1989a). Of these, many show a temperature-sensitive growth phenotype consistent with protein folding defects.…”
Section: Mutations In N-linked Oligosaccharide Synthesis and Processimentioning
confidence: 99%
“…Cells infected with influenza virus were infected and labeled, and the immunoprecipitates were treated with endoglycosidase H (endo H; ICN) as described elsewhere (24). All immunoprecipitations were performed as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
“…While glycoprotein modification in the Golgi apparatus of Saccharomyces cerevisiae differs from that occurring in mammalian cells, the biochemical or enzymatic modifications and processing that occur in the ER are believed to be essentially identical in yeast and mammalian cells (25,30). In all eucaryotic organisms, the initial N-linked glycosylation and subsequent processing of secretory proteins by various glycosyltransferases and glycosidases are part of a complex enzymatic pathway that is not only essential for the correct folding and stability of many proteins (4,17,21,24,36,37) but is in fact coupled with and necessary for the correct routing of some of these proteins to their final destinations (16,26).…”
mentioning
confidence: 99%